Carbonized steel slag phosphogypsum lightweight aggregate anti-radiation ultra-high performance concrete and preparation method thereof

By using carbide steel slag and phosphogypsum as light aggregates in radiation-proof concrete and combining with copper-plated steel fibers, the existing radiation-proof concrete has been solved, and high performance and low-cost radiation-proof concrete has been achieved.

CN119874283AActive Publication Date: 2025-04-25WUHAN UNIV OF TECH
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202510026058.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-25
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

Existing radiation-proof concrete has low strength grades, and the use of heavy metals or high-density aggregates increases production costs and may lead to concrete separation.

Method used

Carbonized steel slag and phosphogypsum are used as light aggregates, combined with copper-plated steel fibers, and light aggregates with core-shell structures are prepared through composite blends and specific preparation processes to improve the flowability and mechanical properties of concrete.

Benefits of technology

Ultra-high performance concrete with good fluidity, high mechanical properties, low shrinkage, and strong anti-neutron radiation ability is achieved, reducing production costs and avoiding the problem of concrete separation.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of cement-based building materials, in particular to carbonized steel slag ardealite lightweight aggregate anti-radiation ultra-high performance concrete and a preparation method thereof.Cement serves as a main cementing material, a composite admixture is added, steel slag and ardealite are used for preparing lightweight aggregate of a core-shell structure, and copper-plated steel fibers are matched, so that the anti-radiation ultra-high performance concrete is prepared. The prepared anti-radiation ultra-high performance concrete is good in fluidity, high in mechanical property, low in shrinkage rate and high in neutron radiation resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cement-based building materials, and in particular to a carbonized steel slag phosphogypsum lightweight aggregate radiation-proof ultra-high performance concrete and a preparation method thereof. Background Art

[0002] With the development and utilization of nuclear energy technology, radiation damage has attracted more attention. Radiation-proof concrete has good shielding capabilities against rays and neutrons. Heavy metals or high-density aggregates are often added during the preparation process. The addition of natural anti-radiation materials will not only increase the cost of concrete production, but the aggregates are often easy to sink in the concrete slurry, causing concrete segregation.

[0003] Industrial production is accompanied by the generation of a large amount of industrial solid waste. Steel slag, fly ash, silica fume, mineral powder, phosphogypsum, etc. have certain activity and can be used as concrete admixtures. However, there is little research on their use in the preparation of radiation-proof concrete.

[0004] Ultra-high performance concrete has the advantages of high mechanical properties and good construction performance, and is often used as special engineering structures. The strength grade of ordinary radiation-proof concrete is usually not higher than C70, and its high performance has yet to be developed. Summary of the invention

[0005] In order to solve the problems existing in the prior art, the present invention provides a carbonized steel slag phosphogypsum lightweight aggregate radiation-proof ultra-high performance concrete. Specifically, the present invention uses cement as the main cementitious material, adds a composite admixture, utilizes steel slag and phosphogypsum to prepare a lightweight aggregate with a core-shell structure, and combines it with copper-plated steel fiber to prepare a radiation-proof ultra-high performance concrete with good fluidity, high mechanical properties, low shrinkage, and strong neutron radiation protection ability.

[0006] Specifically, the carbonized steel slag phosphogypsum lightweight aggregate radiation-proof ultra-high performance concrete of the present invention is composed of the following raw materials in parts by weight: 400-500 parts of cement, 10-50 parts of metakaolin, 50-100 parts of silica fume, 50-100 parts of fly ash, 5-50 parts of copper slag powder, 400-450 parts of carbonized steel slag phosphogypsum lightweight aggregate, 180-250 parts of copper-plated steel fiber, 300-700 parts of coarse sand, 260-400 parts of medium sand, 20-35 parts of water reducer, and 160-180 parts of water.

[0007] The present invention adds metakaolin and copper slag powder, and the metakaolin is rich in amorphous SiO 2 and A l 2 O 3, is an admixture with high volcanic ash properties. These amorphous molecules can effectively fill the internal pores of the mortar and promote subsequent hydration, thereby improving the strength. Kaolin, as an auxiliary additive, can also improve the rheology, mechanics and durability of concrete. Copper slag contains a large amount of calcium oxide, which generates calcium hydroxide when it meets water, and can generate more calcium sulfonate with metakaolin. Calcium sulfonate contains 32 crystal waters, and metakaolin can also bond the crystal water to make it more stable, which is beneficial for protection against neutron radiation.

[0008] Preferably, the carbonized steel slag phosphogypsum lightweight aggregate preparation process is:

[0009] a. Mix 40-70 parts of phosphogypsum, 8-12 parts of cement, 2-5 parts of mineral powder, 1-2 parts of aluminum ash, and 0.1-0.2 parts of calcium borate to obtain a ball core mixture. Mix 35-45 parts of steel slag powder, 2-5 parts of silica ash, 8-10 parts of cement, and 3-5 parts of sodium silicate to obtain a ball shell mixture.

[0010] b. Add the core mixture to the disc granulator, spray water and granulate at a water-binder ratio of 0.2-0.25 to obtain 1-2.36mm cores, add the shell mixture, continue spraying water and granulating at a water-binder ratio of 0.25-0.27 to obtain 2.5-4.75mm billets.

[0011] c. Subject the ball blank to natural curing, carbonization curing and standard curing.

[0012] The present invention adopts phosphogypsum, cement, mineral powder, aluminum ash and calcium borate as raw materials for the core, and steel slag powder, silica ash, cement and sodium silicate as raw materials for the shell. A large amount of industrial waste is used. Phosphogypsum and sodium silicate also have excitation characteristics, which can improve the mechanical properties of lightweight aggregates. Carbonation curing can eliminate the instability of steel slag and optimize the pore structure of lightweight aggregates. In addition, phosphogypsum has a high content of crystal water and contains a small amount of heavy metal elements, which has a shielding effect on neutron rays. The addition of aluminum ash and calcium borate can adjust the hydration products of the shell raw materials, which helps to coordinate phosphogypsum, cement and mineral powder to improve the mechanical properties and radiation resistance of the core. The light aggregate has a water storage and release function and is spherical, which can effectively improve the fluidity of the slurry, exert the internal curing performance, and is conducive to the improvement of the radiation resistance effect.

[0013] Preferably, the cement is ordinary Portland cement with a strength grade of 52.5 or above.

[0014] Preferably, the specific surface area of ​​the metakaolin is not less than 600m 2 / kg.

[0015] Preferably, the SiO in the silica ash 2 The content is more than 90wt%.

[0016] Preferably, the 28d activity index of the fly ash is ≥100%.

[0017] Preferably, the copper slag powder has a specific surface area of ​​650-800m 2 / kg.

[0018] Preferably, the coarse sand particle size is 1.18-2.36 mm.

[0019] Preferably, the medium sand particle size is 0.6-1.18 mm.

[0020] Preferably, the water reducing agent is a polycarboxylic acid high performance water reducing agent, and the water reducing rate is ≥35%.

[0021] Preferably, the CaSO in the phosphogypsum 4 ·2H 2 O content ≥ 80%, SiO 2 Content ≥15%.

[0022] Preferably, the γ-C 2 S content ≥82%, ignition loss ≤2.2%, particle size 50-200μm.

[0023] Preferably, the natural curing time in step c is 24-48 hours.

[0024] Preferably, during the carbonization curing process in step c, CO 2 The pressure is ≥0.4MPa and the curing time is 15-20h.

[0025] Preferably, step c is subjected to standard curing for 28 days.

[0026] Preferably, the saturated water absorption rate of the carbonized steel slag phosphogypsum lightweight aggregate is ≤9%.

[0027] The present invention also relates to a method for preparing the carbonized steel slag phosphogypsum lightweight aggregate radiation-proof ultra-high performance concrete, which specifically comprises the following steps:

[0028] 1) Weigh each raw material by weight,

[0029] 2) Add carbonized steel slag phosphogypsum lightweight aggregate and appropriate amount of water into the mixer for pre-wetting.

[0030] 3) Add cement, metakaolin, silica fume, fly ash, copper slag powder to the mixer, mix evenly, add coarse sand, medium sand, copper-plated steel fiber, mix evenly,

[0031] 4) Add the water reducing agent to the remaining water and mix well to obtain the admixture solution.

[0032] 5) Add the additive solution into the mixer and mix well to obtain slurry.

[0033] 6) Vibrate the slurry into shape, remove the mold after curing, and cure to the specified age.

[0034] Preferably, in step 6), the mold is removed after curing for 1 day.

[0035] Preferably, the age specified in step 6) is 28 days.

[0036] The present invention has the following technical advantages:

[0037] 1. The present invention uses a large amount of industrial solid waste as raw materials for preparing cementitious materials and light aggregates, thus achieving cost reduction and waste utilization.

[0038] 2. The carbonized steel slag phosphogypsum lightweight aggregate of the present invention has good internal curing and radiation protection enhancement effects.

[0039] 3. The concrete of the present invention has the advantages of good fluidity, high mechanical properties, low shrinkage, and strong neutron radiation resistance, and belongs to ultra-high performance concrete. DETAILED DESCRIPTION

[0040] In order to characterize the technical effect of the present invention, concrete was prepared and its performance was tested. During the test, P·O52.5 cement was used, the coarse sand particle size was 1.18-2.36mm, the medium sand particle size was 0.6-1.18mm, the water reducer was polycarboxylic acid high-performance water reducer, the water reduction rate was 36%, and the CaSO in the phosphogypsum was 1.5%. 4 ·2H 2 O content is 80.6%, SiO 2 Content ≥16.3%, γ-C in steel slag powder 2 The S content is 84.6%, the ignition loss is 2.1%, and the particle size is 50-200μm.

[0041] Example 1

[0042] Concrete is composed of the following raw materials in parts by weight: 460 parts of cement, 20 parts of metakaolin, 50 parts of silica fume, 60 parts of fly ash, 50 parts of copper slag powder, 420 parts of carbonized steel slag phosphogypsum lightweight aggregate, 200 parts of copper-plated steel fiber, 600 parts of coarse sand, 400 parts of medium sand, 33 parts of water reducer, and 170 parts of water.

[0043] The preparation process of carbonized steel slag phosphogypsum lightweight aggregate is as follows:

[0044] a. Mix 60 parts of phosphogypsum, 12 parts of cement, 2 parts of mineral powder, 2 parts of aluminum ash, and 0.1 parts of calcium borate to obtain a ball core mixture. Mix 40 parts of steel slag powder, 2 parts of silica ash, 8 parts of cement, and 4 parts of sodium silicate to obtain a ball shell mixture.

[0045] b. Add the core mixture to the disc granulator, spray water at a water-binder ratio of 0.22 to obtain 1-2.36mm cores, add the shell mixture, continue spraying water at a water-binder ratio of 0.25 to obtain 2.5-4.75mm billets.

[0046] c. Natural curing of the ball for 24 hours, CO 2 Carbonization curing at partial pressure of 0.4MPa for 18h and standard curing for 28d are carried out to obtain the product.

[0047] After testing, the initial expansion of the concrete is 670mm, the 28d compressive strength is 128MPa, the flexural strength is 17.3MPa, and the drying shrinkage is 300×10 -6 , chloride ion diffusion coefficient 0.03×10 -12 m 2 / s, when the energy of neutron beam is 14MeV, ∑R≥0.095cm -1 , HVT / cm≤5.3, TVT / cm≤18.0.

[0048] Example 2

[0049] Concrete is composed of the following raw materials in parts by weight: 400 parts of cement, 50 parts of metakaolin, 70 parts of silica fume, 100 parts of fly ash, 30 parts of copper slag powder, 420 parts of carbonized steel slag phosphogypsum lightweight aggregate, 210 parts of copper-plated steel fiber, 600 parts of coarse sand, 380 parts of medium sand, 32 parts of water reducer, and 170 parts of water.

[0050] The preparation process of carbonized steel slag phosphogypsum lightweight aggregate is as follows:

[0051] a. Mix 50 parts of phosphogypsum, 8 parts of cement, 3 parts of mineral powder, 1.5 parts of aluminum ash, and 0.2 parts of calcium borate to obtain a ball core mixture. Mix 40 parts of steel slag powder, 4 parts of silica ash, 9 parts of cement, and 5 parts of sodium silicate to obtain a ball shell mixture.

[0052] b. Add the core mixture to the disc granulator, spray water at a water-binder ratio of 0.22 to obtain 1-2.36mm cores, add the shell mixture, continue spraying water at a water-binder ratio of 0.26 to obtain 2.5-4.75mm billets.

[0053] c. Natural curing of the ball for 24 hours, CO 2 Carbonization curing at partial pressure of 0.4MPa for 18h and standard curing for 28d are carried out to obtain the product.

[0054] After testing, the initial expansion of the concrete was 660mm, the 28d compressive strength was 123MPa, the flexural strength was 16.0MPa, and the drying shrinkage was 325×10 -6 , chloride ion diffusion coefficient 0.04×10 -12 m 2 / s, when the energy of neutron beam is 14MeV, ∑R≥0.100cm -1 , HVT / cm≤5.5, TVT / cm≤17.5.

[0055] Comparative Example 1

[0056] Concrete is composed of the following raw materials by weight: 480 parts of cement, 50 parts of silica fume, 110 parts of fly ash, 420 parts of carbonized steel slag phosphogypsum lightweight aggregate, 200 parts of copper-coated steel fiber, 600 parts of coarse sand, 400 parts of medium sand, 33 parts of water reducer, and 170 parts of water.

[0057] The preparation process of carbonized steel slag phosphogypsum lightweight aggregate is as follows:

[0058] a. Mix 60 parts of phosphogypsum, 12 parts of cement, 2 parts of mineral powder, 2 parts of aluminum ash, and 0.1 parts of calcium borate to obtain a ball core mixture. Mix 40 parts of steel slag powder, 2 parts of silica ash, 8 parts of cement, and 4 parts of sodium silicate to obtain a ball shell mixture.

[0059] b. Add the core mixture to the disc granulator, spray water at a water-binder ratio of 0.22 to obtain 1-2.36mm cores, add the shell mixture, continue spraying water at a water-binder ratio of 0.25 to obtain 2.5-4.75mm billets.

[0060] c. Natural curing of the ball for 24 hours, CO 2 Carbonization curing at partial pressure of 0.4MPa for 18h and standard curing for 28d are carried out to obtain the product.

[0061] After testing, the initial expansion of the concrete was 630mm, the 28d compressive strength was 96MPa, the flexural strength was 13.1MPa, and the drying shrinkage was 465×10 -6 , chloride ion diffusion coefficient is 0.11×10 -12 m 2 / s, when the energy of neutron beam is 14MeV, ∑R≥0.075cm -1 , HVT / cm≤6.5, TVT / cm≤19.0.

[0062] Comparative Example 2

[0063] The concrete is composed of the following raw materials in parts by weight: 460 parts of cement, 20 parts of metakaolin, 50 parts of silica fume, 60 parts of fly ash, 50 parts of copper slag powder, 420 parts of 2.5-4.75 mm fly ash ceramsite, 200 parts of copper-plated steel fiber, 600 parts of coarse sand, 400 parts of medium sand, 33 parts of water reducer and 170 parts of water.

[0064] After testing, the initial expansion of the concrete is 600mm, the 28d compressive strength is 79MPa, the flexural strength is 8.5MPa, and the drying shrinkage is 570×10 -6, chloride ion diffusion coefficient is 0.16×10 -12 m 2 / s, when the energy of neutron beam is 14MeV, ∑R≥0.080cm -1 , HVT / cm≤7.4, TVT / cm≤20.0.

[0065] Comparative Example 3

[0066] Concrete is composed of the following raw materials in parts by weight: 460 parts of cement, 20 parts of metakaolin, 50 parts of silica fume, 60 parts of fly ash, 50 parts of copper slag powder, 420 parts of carbonized steel slag phosphogypsum lightweight aggregate, 200 parts of copper-plated steel fiber, 600 parts of coarse sand, 400 parts of medium sand, 33 parts of water reducer, and 170 parts of water.

[0067] The preparation process of carbonized steel slag phosphogypsum lightweight aggregate is as follows:

[0068] a. Mix 60 parts of phosphogypsum, 20 parts of cement, 2 parts of mineral powder, 2 parts of aluminum ash, 40 parts of steel slag powder, 2 parts of silica ash, and 4 parts of sodium silicate to obtain a mixture.

[0069] b. Add the mixture into the disc granulator and granulate it by spraying water at a water-binder ratio of 0.24 to obtain 2.5-4.75mm pellets.

[0070] c. Natural curing of the ball for 24 hours, CO 2 Carbonization curing at partial pressure of 0.4MPa for 18h and standard curing for 28d are carried out to obtain the product.

[0071] After testing, the initial expansion of the concrete was 620mm, the 28d compressive strength was 83MPa, the flexural strength was 8.9MPa, and the drying shrinkage was 490×10 -6 , chloride ion diffusion coefficient 0.18×10 -12 m 2 / s, when the energy of neutron beam is 14MeV, ∑R≥0.080cm -1 , HVT / cm≤7.2, TVT / cm≤19.5.

[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A carbonized steel slag phosphogypsum lightweight aggregate radiation-proof ultra-high performance concrete, characterized in that: It is composed of the following raw materials in parts by weight: 400-500 parts of cement, 10-50 parts of metakaolin, 50-100 parts of silica fume, 50-100 parts of fly ash, 5-50 parts of copper slag powder, 400-450 parts of carbonized steel slag phosphogypsum lightweight aggregate, 180-250 parts of copper-plated steel fiber, 300-700 parts of coarse sand, 260-400 parts of medium sand, 20-35 parts of water reducer, 160-180 parts of water, The carbonized steel slag phosphogypsum lightweight aggregate preparation process is: a. Mix 40-70 parts of phosphogypsum, 8-12 parts of cement, 2-5 parts of mineral powder, 1-2 parts of aluminum ash, and 0.1-0.2 parts of calcium borate to obtain a ball core mixture. Mix 35-45 parts of steel slag powder, 2-5 parts of silica ash, 8-10 parts of cement, and 3-5 parts of sodium silicate to obtain a ball shell mixture. b. Add the core mixture to the disc granulator, spray water and granulate at a water-binder ratio of 0.2-0.25 to obtain 1-2.36mm cores, add the shell mixture, continue spraying water and granulating at a water-binder ratio of 0.25-0.27 to obtain 2.5-4.75mm billets. c. Subject the ball blank to natural curing, carbonization curing and standard curing.

2. The carbonized steel slag phosphogypsum lightweight aggregate radiation-proof ultra-high performance concrete according to claim 1, characterized in that: The cement is ordinary Portland cement with a strength grade of 52.5 or above.

3. The carbonized steel slag phosphogypsum lightweight aggregate radiation-proof ultra-high performance concrete according to claim 1, characterized in that: The specific surface area of ​​the metakaolin is not less than 600m 2 / kg, the content of SiO2 in the silica ash is above 90wt%, the 28d activity index of the fly ash is ≥100%, and the specific surface area of ​​the copper slag powder is 650-800m 2 / kg.

4. The carbonized steel slag phosphogypsum lightweight aggregate radiation-proof ultra-high performance concrete according to claim 1, characterized in that: The coarse sand particle size is 1.18-2.36 mm, and the medium sand particle size is 0.6-1.18 mm.

5. The carbonized steel slag phosphogypsum lightweight aggregate radiation-proof ultra-high performance concrete according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid high performance water reducing agent with a water reducing rate of ≥35%.

6. The carbonized steel slag phosphogypsum lightweight aggregate radiation-proof ultra-high performance concrete according to claim 1, characterized in that: The CaSO4·2H2O content in the phosphogypsum is ≥80%, and the SiO2 content is ≥15%.

7. The carbonized steel slag phosphogypsum lightweight aggregate radiation-proof ultra-high performance concrete according to claim 1, characterized in that: The γ-C2S content in the steel slag powder is ≥82%, the ignition loss is ≤2.2%, and the particle size is 50-200 μm.

8. The carbonized steel slag phosphogypsum lightweight aggregate radiation-proof ultra-high performance concrete according to claim 1, characterized in that: The natural curing time in step c is 24-48 hours, the CO2 pressure during carbonization curing is ≥0.4MPa, the curing time is 15-20 hours, and the standard curing is up to 28 days.

9. The carbonized steel slag phosphogypsum lightweight aggregate radiation-proof ultra-high performance concrete according to claim 1, characterized in that: The saturated water absorption rate of carbonized steel slag phosphogypsum lightweight aggregate is ≤9%.

10. The method for preparing the carbonized steel slag phosphogypsum lightweight aggregate radiation-proof ultra-high performance concrete according to any one of claims 1 to 9, characterized in that: The steps include: 1) Weigh each raw material by weight, 2) Add carbonized steel slag phosphogypsum lightweight aggregate and appropriate amount of water into the mixer for pre-wetting. 3) Add cement, metakaolin, silica fume, fly ash, copper slag powder to the mixer, mix evenly, add coarse sand, medium sand, copper-plated steel fiber, mix evenly, 4) Add the water reducing agent to the remaining water and mix well to obtain the admixture solution. 5) Add the additive solution into the mixer and mix well to obtain slurry. 6) Vibrate the slurry into shape, remove the mold after curing, and cure to the specified age.

Citation Information

Patent Citations

  • Lightweight material for railroad bed and preparation method thereof

    CN110483096A

  • Solid waste-based unfired high-strength ceramsite and preparation method thereof

    CN113200731A

  • Geopolymer pervious concrete and preparation method thereof

    CN113480245A

  • Concrete prepared from high-activity superfine copper tailing cement mineral admixture

    CN114804771A

  • Anti-gamma-ray ultra-high performance concrete based on anti-radiation functional aggregate and preparation method of anti-gamma-ray ultra-high performance concrete

    CN115579163A